Introgression maintains the genetic integrity of the mating-type determining chromosome of the fungus Neurospora tetrasperma - Corcoran, Pádraic; Anderson, Jennifer L.; Jacobson, David J.; Sun, Yu; Ni, Peixiang; Lascoux, Martin; Johannesson, Hanna (Genome Research, 2016)
Genome evolution is driven by a complex interplay of factors, including selection, recombination, and introgression. The regions determining sexual identity are particularly dynamic parts of eukaryotic genomes that are prone to molecular degeneration associated with suppressed recombination. In the fungus Neurospora tetrasperma, it has been proposed that this molecular degeneration is counteracted by the introgression of nondegenerated DNA from closely related species. In this study, we used comparative and population genomic analyses of 92 genomes from eight phylogenetically and reproductively isolated lineages of N. tetrasperma, and its three closest relatives, to investigate the factors shaping the evolutionary history of the genomes. We found that suppressed recombination extends across at least 6 Mbp (∼63%) of the mating-type (mat) chromosome in N. tetrasperma and is associated with decreased genetic diversity, which is likely the result primarily of selection at linked sites. Furthermore, analyses of molecular evolution revealed an increased mutational load in this region, relative to recombining regions. However, comparative genomic and phylogenetic analyses indicate that the mat chromosomes are temporarily regenerated via introgression from sister species; six of eight lineages show introgression into one of their mat chromosomes, with multiple Neurospora species acting as donors. The introgressed tracts have been fixed within lineages, suggesting that they confer an adaptive advantage in natural populations, and our analyses support the presence of selective sweeps in at least one lineage. Thus, these data strongly support the previously hypothesized role of introgression as a mechanism for the maintenance of mating-type determining chromosomal regions.